High Cholesterol Awareness, Treatment, and Control Among Hispanic/Latinos: Results From the Hispanic Community Health Study/Study of Latinos - Rodriguez, Carlos J (J Am Heart Assoc, 2015)
BACKGROUND: We assessed high cholesterol (HC) awareness, treatment, and control rates among US Hispanic/Latino adults and describe factors associated with HC awareness and management. METHODS AND RESULTS: Baseline data (collected 2008–2011) from a multisite probability sample of Hispanic/Latino adults in the Hispanic Community Health Study/Study of Latinos (18 to 74 years old; N=16 207) were analyzed. HC was defined as low-density lipoprotein-cholesterol ≥130 mg/dL and/or total cholesterol ≥240 mg/dL or use of cholesterol-lowering medication. Among Hispanic/Latino adults with HC, almost half (49.3%) were not aware of their condition and only 29.5% were receiving treatment. Men had a higher HC prevalence than women (44.0% versus 40.5%) but a lower rate of treatment (28.1% versus 30.6%). Younger adults were significantly less likely to be HC aware compared to those who were older. Those with hypertension, diabetes, and high socioeconomic position were more likely to be HC aware. US-born Hispanic/Latino were more likely to be HC unaware than foreign-born Hispanics/Latinos, but longer US residency was significantly associated with being HC aware, treated, and controlled. Cholesterol control was achieved among 64.3% of those who were HC treated. However, younger adults, women, those with lower income, those uninsured, and more recent immigrants were less likely to be HC controlled. Individuals of Puerto Rican or Dominican background were most likely to be HC aware and treated, whereas those of Mexican or Central American background were least likely to be HC treated. Individuals of Cuban and South American background had the lowest rates of HC control, whereas Puerto Ricans had the highest. CONCLUSIONS: Understanding gaps in HC awareness, treatment, and control among US Hispanic/Latino adults can help inform physicians and policymakers to improve disease management and patient education programs.